Barriers to a Healthy Diet. Issue 5 (September 2018) - Snow, Denise
Abstract : A thorough nutritional assessment by nurses can identify barriers to a healthy diet for women and their families. A substantial barrier to effective patient counseling is lack of consideration of patients' resources including constraints of access, time, and cost of healthier choices. Our nutrition expert, Denise Snow, covers the essential parts of this type of assessment and offers suggestions for making dietary changes based on available resources.